THE STUDY ON THE INHERITANCE AND DEVELOPMENT OF HUNAN DAOZHOU DIAOZI OPERA - cheng, Zhuwei; Siriwongsuwan, Rungkiat (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2025)
Introduction: The Hunan Daozhou Diaozi Opera is more than just a folk performance art; it is a cultural treasure that portrays the interaction of music, society, and cultural power in Chinese society. Objective: To study on the inheritance and development of Hunan Daozhou Diaozi Opera. Methods: The researcher used data from numerous secondary sources to assess and synthesize the study’s findings. Documentary research data includes books, other documents, and written records. this investigation. The documentary research approach necessitated gathering information from books and articles that identified ten relevant sources, all of which were verified for trustworthiness by specialists. This paper investigates the historical evolution of Hunan melodic opera in China, its context in various periods of Chinese history, and suggests rules for maintaining and propagating the country’s traditional folk music. Results: Chinese folk music is an integral part of China’s rich traditional culture, the spiritual lifeline and inner core of the country, and the foundation for our long-term stability in the face of global cultural instability. This is because, according to Mei Wang (2020), our country’s methods for integrating and preserving regional opera traditions are uncertain. We must constantly increase the processes for building and sustaining traditional opera culture, followed by the construction of systems to preserve it. This study is congruent with the findings of Juan Xue (2017), who discovered that the inheritance and development of Chinese regional opera is an important and rich cultural history, with practical implications that can effectively promote the inheritance and development of traditional styles. Conclusion: The study’s findings reveal that Diaozi Dao opera is used to transmit the local community’s identity, shared memories, and worldview. Music and performance not only reflect social and historical contexts but also serve as a forum for negotiating meaning between tradition and present change.